Remifentanil Induces Cardio Protection Against Ischemia/Reperfusion Injury by Inhibiting Endoplasmic Reticulum Stress Through the Maintenance of Zinc Homeostasis. (July 2018) - Sheng, Mingwei; Zhang, Ge; Wang, Jiannan; Yang, Qing; Zhao, Huanhuan; Cheng, Xinxin; Xu, Zhelong
Abstract : BACKGROUND: Although it is well known that remifentanil (Rem) elicits cardiac protection against ischemia/reperfusion (I/R) injury, the underlying mechanism remains unclear. This study tested if Rem can protect the heart from I/R injury by inhibiting endoplasmic reticulum (ER) stress through the maintenance of zinc (Zn 2+ ) homeostasis. METHODS: Isolated rat hearts were subjected to 30 minutes of regional ischemia followed by 2 hours of reperfusion. Rem was given by 3 consecutive 5-minute infusions, and each infusion was followed by a 5-minute drug-free perfusion before ischemia. Total Zn 2+ concentrations in cardiac tissue, cardiac function, infarct size, and apoptosis were assessed. H9c2 cells were subjected to 6 hours of hypoxia and 2 hours of reoxygenation (hypoxia/reoxygenation [H/R]), and Rem was given for 30 minutes before hypoxia. Metal-responsive transcription factor 1 (MTF1) overexpression plasmids were transfected into H9c2 cells 48 hours before hypoxia. Intracellular Zn 2+ level, cell viability, and mitochondrial injury parameters were evaluated. A Zn 2+ chelator N, N, N′, N′-tetrakis-(2-pyridylmethyl) ethylenediamine (TPEN) or an ER stress activator thapsigargin was administrated during in vitro and ex vivo studies. The regulatory molecules related to Zn 2+ homeostasis and ER stress in cardiac tissue, and cardiomyocytes were analyzed by Western blotting. RESULTS: Rem caused significant reversion of Zn 2+ loss from the heart (Rem + I/R versus I/R, 9.43 ± 0.55 vs 7.53 ± 1.18; P < .05) by suppressing the expression of MTF1 and Zn 2+ transporter 1 (ZnT1). The inhibited expression of ER stress markers after Rem preconditioning was abolished by TPEN. Rem preconditioning improved the cardiac function accompanied by the reduction of infarct size (Rem + I/R versus I/R, 21% ± 4% vs 40% ± 6%; P < .05). The protective effects of Rem could be reserved by TPEN and thapsigargin. Similar effects were observed in H9c2 cells exposed to H/R. In addition, MTF1 overexpression blocked the inhibitory effects of Rem on ZnT1 expression and ER stress at reoxygenation. Rem attenuated the collapse of mitochondrial membrane potential (ΔΨm) and the generation of mitochondrial reactive oxygen species by inhibiting ER stress via cardiac Zn 2+ restoration (Rem + H/R versus H/R, 79.57% ± 10.62% vs 58.27% ± 4.32%; P < .05). CONCLUSIONS: Rem maintains Zn 2+ homeostasis at reperfusion by inhibiting MTF1 and ZnT1 expression, leading to the attenuation of ER stress and cardiac injury. Our findings provide a promising therapeutic approach for managing acute myocardial I/R injury.